The Novel Crohn's Disease Marker Anti-GP2 Antibody Is Associated with Ileocolonic Location of Disease - Valentina Somma; Hani Ababneh; Ahmad Ababneh; Simona Gatti; Vittorio Romagnoli; Emanuele Bendia; Karsten Conrad; Dimitrios P. Bogdanos; Dirk Roggenbuck; Gino Ciarrocchi (Gastroenterology Research and Practice)
Crohn's disease (CD) is an inflammatory bowel disease (IBD) that can affect the whole gastrointestinal tract. The ileocolonic variant of CD, an inflammation of both the ileum and the large intestine, accounts for up to 50% of the cases with CD, whereas Crohn's ileitis affecting the ileum is diagnosed in about 30%. Crohn's colitis, which is confined to the large intestine and accounts for the remaining 20%, is difficult to distinguish from the large bowel inflammation seen in patients with ulcerative colitis (UC). The pathogenesis of CD is not yet completely understood. Autoimmunity is one factor that can partake in the triggering or modulation of inflammatory processes in IBD. The major zymogen-granule membrane glycoprotein 2 (GP2) has been recently identified as a major autoantigenic target in CD. Interestingly, GP2 is mainly expressed in the pancreas and has also been demonstrated to be a membrane-anchored receptor of microfold cells in the follicle-associated epithelium. Remarkably, GP2 is overexpressed at the site of CD inflammation in contrast to the one in UC. By utilizing novel enzyme-linked immunosorbent assays for the detection of GP2-specific IgA and IgG, the loss of tolerance to GP2 has been associated with a specific clinical phenotype in CD, in particular with the ileocolonic location of the disease.